2017
DOI: 10.1177/1203475417690719
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Syndrome: Clinical Features, Histopathology, and Associations of 83 Cases

Abstract: All patients with SS deserve careful investigation of possible underlying conditions. Higher ESR and lower hemoglobin levels might reinforce the need of malignancy screening. Also, leukocytoclasia appears to be a potential marker of higher recurrence rate, demanding closer and longer follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 23 publications
3
9
3
1
Order By: Relevance
“…This criterion was fulfilled in the present study, in the original eight cases published by Dr. Sweet, and in many other studies including the most recent article by Casarin Costa et al. who reported the absence of leukocytoclastic vasculitis in their cohort of 83 patients. On the other hand, other authors have reported leukocytoclastic vasculitis in a variable number of patients, including Rochael et al.…”
Section: Discussionsupporting
confidence: 69%
“…This criterion was fulfilled in the present study, in the original eight cases published by Dr. Sweet, and in many other studies including the most recent article by Casarin Costa et al. who reported the absence of leukocytoclastic vasculitis in their cohort of 83 patients. On the other hand, other authors have reported leukocytoclastic vasculitis in a variable number of patients, including Rochael et al.…”
Section: Discussionsupporting
confidence: 69%
“…In this study, we observed that Sweet syndrome was more frequent in the women, and the mean age at diagnosis was 53 years, consistent with the data described in the literature (10)(11)(12)(13). Our results failed to show significant differences in age and sex in the patients of Sweet syndrome with and without hematologic malignancy.…”
Section: Discussionsupporting
confidence: 91%
“…In our cohort, fever was notably more common than other clinical symptoms (24/37, 65%), with a higher incidence than that in some studies (11)(12)(13), emphasizing that fever exists as an important diagnostic criterion of Sweet syndrome (3,4). Our study obtained a positive association with arthralgia in only 5% of the patients, none of whom had Sweet syndrome with hematologic malignancy.…”
Section: Aml* Comparison Of Hemoglobin and Platelet Levels Between Ssupporting
confidence: 41%
See 1 more Smart Citation
“…Dieses Kriterium war bei der vorliegenden Studie, bei den ursprünglichen acht von Dr. Sweet veröffentlichten Fällen und bei vielen anderen Studien erfüllt, einschließlich des neuesten Artikels von Casarin‐Costa et al. , die bei ihrer Kohorte von 83 Patienten keine leukozytoklastische Vaskulitis feststellen konnten. Andererseits haben andere Autoren eine leukozytoklastische Vaskulitis bei einer unterschiedlichen Anzahl von Patienten beschrieben, unter anderem Rochael et al.…”
Section: Diskussionunclassified